Fatwa dan Regulasi Perbankan Syari'ah Indonesia - Oyo Sunaryo Mukhlas (STAI Siliwangi Bandung, 2020)
The development of Islamic banking would require a significant consequence for the immediate issuance of a regulation that can be used as legal or juridical basis in the implementation. So well recognized, the economic system of Shari'ah also juridical legitimacy of government Publication of a rule of Shari'ah economy also depends on the policies made by the power regime that the existence of the accommodating attitude of government in the form of policies that accommodate the interests of the Muslims. The charges against the establishment of laws that regulate the economy Shari'ah is a long struggle of Muslims, as well as controversy and polemic, the implementation of Shariah economic system is also a major challenge in the technical and practical level that demands the hard struggle of practitioners and academics to formulate a good concept